Morphological Variation in Tupaia glis from the East and the West Coast of Peninsular Malaysia - Nurul Farah Diyana Ahmad Tahir (2013)
Peninsular Malaysia is primarily divided into east and west coast by the Titiwangsa Range (Oon, 2008; Breemen, 2008). This mountainous and forested area would probably be an effective geographical barrier to the dispersal of small mammals from east and west coast of Peninsular Malaysia. Such barrier can have several consequences on the geographical variation and speciation of widespread mammals as long term isolation can result in morphological variation within species. Thus, in this study, a morphometric approaches is used to investigate the morphological variation of T. glis from the east and west coast of Peninsular Malaysia to understand whether isolating effect of Titiwangsa Range is contributing in the morphological variation in this species. Hence, Discriminant Function Analysis (DFA) is used in order creating the method in identifying the morphological variation of the T. glis samples. From this study, it is found that there are three (3) characteristics of the T. glis which are the HB, SL and C1M3L had the highest discriminant level, and this was reflected by the importance of these characters during the identification process. Besides, there are two main groups of forms were found after the cluster analysis were run on the samples. But the species of the forms are still not identified and confirmed.